The Lisbon Treaty and the Accession of Turkey to the European Union - Alves, Luísa Verdelho (Journal of Business and Legal Sciences / Revista de Ciências Empresariais e Jurídicas, 2011)
On December 13, 2007, the Member States of the European Union (EU) signed in Lisbon a treaty amending the founding Treaties of the EU. After a troubled ratification process, due to the adverse outcome of a national referendum in Ireland, the Lisbon Treaty finally entered into force on December 1, 2009, defining a new trajectory for the EU integration process. The present article addresses the possible implications of the recent EU treaty reform to the accession of Turkey to the EU. To that end, I propose an analysis of the modifications introduced in the institutional framework of the Union and I inquire whether the legal change at this level is capable of influencing the attitude of the current Member States concerning the accession of Turkey to the EU.